Symposium report international symposium on wellness and heal thy lifestyle - Tengku Alina, Tengku Ismail
Dumbbell exercise and missile nutrition of a high-protein snack to prevent obesity as well as sarcopenia and osteopenia (Masashige Suzuki, School of Sports Science, Waseda University, Japan) In 1983, Suzuki has developed the Dumbbell exercise for his dieting; weight reduction from 200 lb to 167 lb in 5 months and maintaining the reduced body weight for the past 25 years. It is an appropriate exercise for children, middle-aged and old people, because of its easy performance using a very light dumbbell weighing 300g to 2 kg. His study suggested that Dumbbell exercise after the ingestion of a high-protein snack may contribute to prevention of obesity, metabolic syndromes, sarcopenia and osteopenia.